PEMBENTUKAN KATA: PROSES MORFOLOGIS PADA GAIRAIGO - Sa'idatun Nishfullayli (Universitas Diponegoro, 2013)
ABSTRACT This paper describes the morphological processes of a Japanese vocabulary, gairaigo. Gairaigo is absorbed from foreign languages, other than Chinese. There has been an increasing number of Japanese speakers who use the word gairaigo since it is assumed that gairaigo makes people look smarter and more modern. In addition, gairaigo is being used widely because it can serve not only as a single lexeme, but also as the input (root/stem) to form other vocabulary. To determine what morphological processes that can be applied to gairago, the writer used the word formation theory from Tsujimura (2000). Therefore, this paper is a descriptive study. The results show that there are three morphological processes: affixation, compounding, and abbreviation (clipping and contraction). Changes in part of speech (derivation) as a result of certain morphological process are also explained. Changes or distortion of meaning is not discussed in this paper. Key word: gairaigo, affixation, compounding, abbreviation, clipping, contraction.